STUDY OF COMPOSITION AND HOMOGENITY OF Ni80Fe20 PERMALLOY IN THE FORM OF TARGET AND THIN FILM AS MATERIALS OF MAGNETIC SENSORS - Fahru Nurosyid; Budi Purnama (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2005)
STUDY OF COMPOSITION AND HOMOGENITY OF Ni80Fe20 PERMALLOY IN THE FORM OF TARGET AND THIN FILM AS MATERIALS OF MAGNETIC SENSORS. Material fabrication of a ferromagnetic permalloy Ni80Fe20 has successfully been done. The sample was used as a target in magnetic thin film deposition by the sputtering method. The corresponding characterization including spectral analysis with XRF and XRD supports the prediction that the permalloy has been formed. The XRF analysis result shows that the ratio of the target has good agreement with the calculation. The thin film produced by sputtering gave the same characteristic as the target. From the XRD analysis it was shown that Ni80Fe20 permalloy was formed in the target and thin film, they were shown with the peak at the angle of 2θ= 44,4°, at a (111) plane orientation as the hkl plane from Ni80Fe20. There is another peak at the angle 2θ = 37° that was estimated to be ferrosic oxide Fe3O4. This magnetic oxide was formed when the target had been heated at the temperature 350°C-400°C in the free air.